The Influence Of Organizational Culture And Career Development On Employee Performance With Self-Efficiency As A Moderation Variable In Upt Public Relationship Department (PKB Medan Amplas) - Muhammad Farhan; Winda Ardiani; Rizki Putra (Politeknik Ganesha Medan, 2023)
The Influence of Organizational Culture and Career Development on Employee Performance with Self-Efficacy as a Moderating Variable at the UPT Transportation Service (PKB Medan Amplas). The purpose of this study was to determine the effect of career development on employee performance in self-efficacy moderation at the UPT Transportation Service (PKB Medan Amplas). The formulation of the problem in this study is whether career development affects employee performance in moderation by self-efficacy at the UPT Transportation Service (PKB Medan Amplas)?. This study uses data quality test analysis, classical assumption test, multiple regression analysis, t test, F test and determination test, with the help of the SPSS test tool version 22.00. The results of hypothesis testing show that partially, organizational culture variables have a significant effect on employee performance at the UPT Transportation Service (PKB Medan Amplas). 66055 which means that organizational culture has no real (significant) influence on employee performance variables. Partially it is known that the career development variable has a significant effect on employee performance at the UPT Transportation Service (PKB Medan Amplas). real (significant) effect on employee performance variables. The indirect effect of organizational culture on employee performance through self-efficacy has a significant effect on the UPT Transportation Service (PKB Medan Amplas), this is known from the value of the Standardized Beta Coefficient of -0.337 with a significant level of 0.000 <0.05. With the fulfillment of these two conditions, it shows that the variable self-efficacy strengthens the moderation of organizational culture in influencing employee performance. Thus self-efficacy is a moderating variable or a strong variable in moderating the influence of organizational culture on employee performance which indicates that the self-efficacy variable strengthens the moderation of organizational culture in influencing employee performance. The indirect effect of career development on employee performance through self-efficacy has no significant effect on the UPT Transportation Service (PKB Medan Amplas), this is known from the Standardized Beta Coefficient value of -0.095 with a significant level of 0.348 > 0.05. Because one of these conditions is not met, it shows that the variable self-efficacy is not a moderating variable in career development in influencing employee performance. Thus self-efficacy is not a moderating variable in moderating the influence of career development on employee performance which indicates that self-efficacy is not a moderating variable of career development in influencing employee performance.